(untitled) (Journal of Pharmaceutical Negative Results, 2022)
In Malaysia, the use of herbal medicines is common. Among the famous herbal medicine is Eurycoma longifolia (E. longifolia) also locally called Tongkat Ali. As a results of numerous health benefits, the market value for E. longifolia products has grown stronger annually and has emerged as one of the most rapidly growing products in herbal market. The E. longifolia products are added in coffee and tea bags or in the supplementary form of capsules and tablets. Antioxidant properties of E. longifolia in its crude form in different solvents (aqueous and alcohol) have been widely reported but very few studies have looked into the antioxidant properties in the commercial E. longifolia products in capsule form. In this study, aqueous extract of commercial E. longifolia was tested for its antioxidant properties using total phenolic content (TPC) assay, 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay and ferric reducing ability of plasma (FRAP) assay. In the TPC assay, it was found that the Gallic acid equivalent of the E. longifolia tested was 7.3229 mg GAE/g. Meanwhile for the FRAP assay, the ferrous sulphate equivalence (FSE) of E. longifolia tested was 1.095 mM FSE/g. At concentrations of 0.001 g/L, 0.01 g/L, 0.1 g/L, 1 g/L and 10 g/L, the radical scavenging activities of E. longifolia and ascorbic acid (positive control) were 38.90% and 46.79%, 59.25% and 73.66%, 33.07% and 49.32%, 39.46% and 88.43% 50.55% and 90.83% respectively. In conclusion, aqueous extract of commercial E. longifolia shows antioxidant properties comparable to previous studies on E. longifolia crude extracts.